Interrelation of the hammer swing technique with the technique of its previous rotation in highly skilled hammer throwers - Shеsterova, L.; Rozhkov, V. (My University, 2018)
The results of studies on the relationship of the parameters of the hammer swing technique with the biomechanical indicators of the previous hammer rotation techniques are presented. Purpose: investigate the relationship of the hammer swing technique with the previous hammer rotation technique. Material & Methods: analysis and synthesis of scientific and methodical literature, analysis of video materials, methods of mathematical statistics. 7 qualified hammer throwers, finalists of the World Cup and European Cups during the 2016–2018 seasons were investigated. Results: the closest relationship was recorded between the angle of flexion in the right elbow joint and the angular velocity of the hammer (r=0,868), such studied indicators of the hammer assassination technique, such as: angular speed of the hammer, linear speed of the hammer, the center of the hammer force did not have a significant impact on the biomechanical indicators previous hammer rotation. Conclusion: previous hammer rotation techniques are more dependent on the angle of flexion in the left knee, right elbow joints, the height of the hammer layer rising from the support, the size of the left foot turning outwards and the height of the heel of the left foot rising from the support during the hammer wagging.
Shеsterova L. Interrelation of the hammer swing technique with the technique of its previous rotation in highly skilled hammer throwers / L. Shеsterova, V. Rozhkov // Slobozhanskyi herald of science and sport. – 2018. – № 6.(68). – Р. 13–16.
Keywords: throwers, biomechanical parameters, technique, hammer swing, previous hammer rotations.; метатели, биомеханические параметры, техника, замах молота, предвартельные вращения молота; метальники, біомеханічні параметри, техніка, замах молоту, попередні оберти молоту